Invasion consequences and ecology: evaluation of community and environment interactions of an exotic, invasive plant, garlic mustard (Alliaria petiolata). - Morton, Tegan. (2017)
Abstract: Globally, exotic, invasive species are the second leading cause of native species decline. I aimed in this thesis to explore first the resource ecology of a "strong invader" of New England forests, the exotic weed garlic mustard (Alliaria petiolata). Particularly, I aimed to understand to what extent performance differences among populations were explained by limitations imposed by soil nutrient abundance and availability. Secondly, I aimed to understand the potential of a native herbivore () to adapt to community disturbances following garlic mustard and exotic parasitoid invasion to escape an evolutionary trap. Specifically, I focused on the adaptation of larvae to complete development to pupation on the novel host plant that has previously caused population decline. With regards to the first aim, I surveyed several populations of garlic mustard from a variety of habitats in Massachusetts and measured a variety of variables related to soil nutrient availability and plant performance. Overall, soil variables have limited explanatory and predictive power with regards to plant performance. There is some evidence of stronger relative effects of soil pH and potassium availability on performance, however it does not resolve much of the variation among populations. It is likely that other environmental factors, such as light or soil moisture, impose greater limits on performance. To address the second aim, I modified an existing stochastic simulation model to generate a subpopulation of adapted individuals. I applied treatments addressing two issues: (1) the source of genetic variation for the adaptive trait, and (2) the role of top-down regulation by exotic parasitoids in limiting adaptation. Results show that even under high rates of mutation, persistence of adapted individuals is low, and any adaptation observed in natural populations is likely due to residual variation. Secondly, parasitism significantly decreased the likelihood of adaptation, and persistence of adapted individuals was possible at substantial levels only under conditions of enemy free space. Cumulatively, my research shows that for garlic mustard, the abiotic soil environment imposes little limitations on performance and likely this plant can successfully colonize a variety of environments, provided there is a suitable availability of light and water. When it comes to understanding the effect of such colonization and invasion on native community members, my research shows that the community context, particularly the third trophic level, influences greatly predictions for native species persistence and adaptation.; Thesis (M.S.)--Tufts University, 2012.; Submitted to the Dept. of Biology.; Advisor: Colin Orians.; Committee: Frances Chew, and J. Michael Reed.; Keyword: Biology.